KEWENANGAN NOTARIS UNTUK MEREALISASIKAN HAK CIPTA SEBAGAI JAMINAN KREDIT PERBANKAN DI INDONESIA - Prihantiwi, Lidwina Tessa Kurnia (Sekolah Tinggi Ilmu Hukum Sumpah Pemuda, 2025)
This article has a main issue regarding the authority of a notary and the obstacles to realizing copyright as a guarantee for bank credit. The purpose of this article is to identify the subject matter of the article. This article is a normative juridical legal research and has a prescriptive nature. The type of data used is secondary. The data collection techniques used were document study and literature study, then the analysis technique used was the deductive method. The results of the research show that the Notary is a public official ordered by the Copyright Law in his role in making an Authentic Deed relating to Copyright as a Fiduciary Guarantee. Notary is a party that reports money laundering in Indonesia. Notaries have various obstacles in exercising their authority. The suggestion from the author is that the President should be able to make a Government Regulation (PP) which regulates the Copyright Assessment guidelines, assessment agencies, types of copyrights that can be used as Fiduciary Guarantee, risk mitigation mandates notaries to encourage the realization of Copyright as Fiduciary Guarantee and provides special trainings for Notaries in the context of realizing Copyright as Fiduciary Guarantee. The Indonesian Notary Association should discuss the issue of Copyright as a Fiduciary Guarantee in its regular Congress so that the Notary, as one of the parties who has the authority to realize Copyright as a Fiduciary Guarantee, can exercise this authority in real terms.